Multiple medication use in the middle and older age population - Richardson, Kathryn Jane (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Medical Gerontology, 2013)
Polypharmacy in the older population is increasingly common and can represent necessary preventative therapies or potential inappropriate prescribing and be a risk factor for falls. In addition, medications with anti-cholinergic activity have recently been implicated with cognitive and functional decline in older adults, but few studies have examined their relationship with falls. Estimating the associated risks in observational studies is complex due to the accuracy of medication use ascertainment and confounding by indication.
Keywords: Medical Gerontology, Ph.D.; Ph.D. Trinity College Dublin